Hestia: setting a new benchmark for Malaysian aged care services - Azuan Md Ghazali @ Ghazali (2014)
Hestia Care & Retreat (thereafter referred as Hestia) established in early 2014, in the suburb of Petaling Jaya. Hestia is one of Bumiputra partnership enterprise between Ms Sabrina and her partner. The main service is to provide care services for elderly. Their service include daily care, weekly care and permanent resident for bedridden. Beside provide care service, Hestia also providing other services like physiotherapy, transportation and knowledge sharing in order for them to be well balance as senior citizens.